Effects of balanced fertilization on crop production and soil nutrient status under long-term greenhouse eggplant-rice rotation system - WANG qiang; XU Jian-ming; JIANG Li-na; FU Jian-rong; MA Jun-wei; YE Jing; WANG Jianmei (浙江大学学报. 农业与生命科学版)
A field experiment was conducted to study the effects of balanced fertilization on the crop production and soil nutrient status within two crop growing seasons under long-term greenhouse eggplant-rice rotation system. The results showed that N was the main limited factor for soil nutrients at the current stage, while P and K were not the case for crop yields, nutrient absorption and contents in two crop growing seasons. The total accumulation of N overground in optimum treatment (OPT) during the rotation period was 314.2 kg·hm-2, which accounted for 63.0% and 72.9% of supplying amounts of soil N in the period of greenhouse eggplant and rice respectively, and the corresponding apparent use efficiency of N was only 10.85% and 24.9%. The total accumulation of P2O5 and K2O overground during the rotation period were 159.5 and 543.9 kg·hm-2, respectively. The supplying amounts of soil P and K both exceeded 90%, and the apparent use efficiency of P and K was 11.5% and 8.6%, respectively. Both decreasing the N application and delaying the N application time to the rice season could enhance the total nutrient absorption. The suitable nitrogen application rates for the greenhouse eggplant and rice were 450 and 150 kg·hm-2, respectively, decreasing by 55% and 33.3% as compared with the traditional fertilization. The paddy-upland rotation could effectively utilize the soil nutrients which were accumulated by the heavy fertilization in the greenhouse season, but the soil nutrients still had the tendency to move into deeper soil layers.